Biomimetism, biomimetic matrices and the induction of bone formation - Ripamonti, Ugo (J Cell Mol Med, 2009)
Bone formation by induction initiates by invocation of osteogenic soluble molecular signals of the transforming growth factor-β (TGF-β) superfamily; when combined with insoluble signals or substrata, the osteogenic soluble signals trigger the ripple-like cascade of cell differentiation into osteoblastic cell lines secreting bone matrix at site of surgical implantation. A most exciting and novel strategy to initiate bone formation by induction is to carve smart self-inducing geometric concavities assembled within biomimetic constructs. The assembly of a series of repetitive concavities within the biomimetic constructs is endowed with the striking prerogative of differentiating osteoblast-like cells attached to the biomimetic matrices initiating the induction of bone formation as a secondary response. Importantly, the induction of bone formation is initiated without the exogenous application of the osteogenic soluble molecular signals of the TGF-β superfamily. This manuscript reviews the available data on this fascinating phenomenon, i.e. biomimetic matrices that arouse and set into motion the mammalian natural ability to heal thus constructing biomimetic matrices that in their own right set into motion inductive regenerative phenomena initiating the cascade of bone differentiation by induction biomimetizing the remodelling cycle of the primate cortico-cancellous bone.